Substituent effects of auxiliary ligands in mononuclear dibenzoylmethane DyIII/ErIII complexes: single-molecule magnetic behavior and luminescence properties. Issue 45 (4th November 2020) - Liu, Shan-Shan; Liu, Bin; Ding, Man-Man; Meng, Yin-Shan; Jing, Jia-Hui; Zhang, Yi-Quan; Wang, Xincheng; Lin, Shijing
Abstract : The single-molecule magnetic behavior and luminescence of [(dbm)3 Ln(dmbipy)] and [(dbm)2 Ln(dmobipy)(NO3 )] are significantly modified by replacing the substituents of auxiliary ligands. Abstract : Four mononuclear rare earth complexes, [(dbm)3 Ln(dmbipy)] (1-Ln, Ln = Dy, Er) and [(dbm)2 Ln(dmobipy)(NO3 )] (2-Ln, Ln = Dy, Er) (Hdbm = dibenzoylmethane, dmbipy = 4, 4′-dimethyl-2, 2′-bipyridine, dmobipy = 4, 4′-dimethoxy-2, 2′-bipyridine), have been synthesized by tuning the substituents at the 4, 4′-positions of 2, 2′-bipyridine. It is interesting to note that replacing the substituents of auxiliary ligands from –CH3 to –OCH3 results in a major difference in the molecular formula and geometries. Magnetic measurements show that slow relaxation of the magnetization appears clearly in the absence of a dc field for 1-Dy, while under an applied dc field for the others. Ab initio calculations reveal that the calculated effective g z value for 1-Dy is larger than that for 2-Dy, consistent with the experimental results. In addition, the luminescence properties of the four complexes have been studied, and 2-Dy, 1-Er and 2-Er can exhibit characteristic emissions of Dy III /Er III ions.